Nutritional ketoacidosis during incremental exercise in healthy athletes - Dearlove, D; Faull, O; Rolls, E; Clarke, K; Cox, P (Frontiers, 2019)
Purpose: Ketosis, achieved through ingestion of ketone esters, may influence endurance exercise capacity by altering substrate metabolism. However, the effects of ketone consumption on acid-base status and subsequent metabolic and respiratory compensations are poorly described. Methods: Twelve athletically trained individuals completed an incremental bicycle ergometer exercise test to exhaustion following the consumption of either a ketone ester [(R)-3-hydroxybutyrate-(R)-1,3-butanediol] or a taste-matched control drink (bitter flavoured water) in a blinded, cross-over study. Respiratory gases and arterialised blood gas samples were taken at rest and at regular intervals during exercise. Results: Ketone ester consumption increased blood D-β-hydroxybutyrate concentration from 0.2 to 3.7 mM/L (p < 0.01), causing significant falls versus control in blood pH to 7.37 and bicarbonate to 18.5 mM/L before exercise. To compensate for ketoacidosis, minute ventilation was modestly increased (p < 0.05) with non-linearity in the ventilatory response to exercise (ventilatory threshold) occurring at a 22 W lower workload (p < 0.05). Blood pH and bicarbonate concentrations were the same at maximal exercise intensities. There was no difference in exercise performance having consumed the ketone ester or control drink. Conclusion: Athletes compensated for the greater acid load caused by ketone ester ingestion by elevating minute ventilation and earlier hyperventilation during incremental exercise.